Quantum interference among vortex bound states in superconductors - Yi-Ming Fu; Da Wang; Qiang-Hua Wang (New Journal of Physics, 2025)
In a recent experiment (Hou et al 2025 Phys. Rev. X 15 011027), a new type of necklace-like vortex bound state (VBS) was observed and attributed to disorder induced interference among different Caroli–de Gennes–Matricon (CdGM) states within one single vortex. In this work, we further investigate the possibilities of quantum interference among the CdGM states from different vortices in clean superconductors, which may become significant near the upper critical field. We find a series of interference patterns in the local density of states (LDOS) due to the overlap between spatially separated individual CdGM states. On a vortex lattice, the interference can also lead to a necklace-like LDOS, hence, providing an alternative and intrinsic mechanism to observe the novel necklace-like, or other spatially modulated VBS more generally, in experiments. These results can be understood quite well within an effective tight-binding model constructed from the individual CdGM states, and can be checked in future experiments.